2014
DOI: 10.1021/jp412654s
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Oxidation via Chlorine, Bromine, and Iodine under Atmospheric Conditions: Thermochemistry and Kinetics

Abstract: Emissions of gaseous mercury from combustion sources are the major source of Hg in the atmosphere and in environmental waters and soils. Reactions of Hg(o)(g) with halogens are of interest because they relate to mercury and ozone depletion events in the Antarctic and Arctic early spring ozone hole events, and the formation of Hg-halides (HgX2) is a method for removal of mercury from power generation systems. Thermochemistry and kinetics from published theoretical and experimental studies in the literature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…On the one hand, high wind speed may increase the levels of halogen atoms (Br and Cl etc.) and sea salt aerosols in the marine atmosphere, which in turn were favorable to the production of RGM and formation of Hg P 2.5 (Auzmendi-Murua et al, 2014); on the other hand, high wind speed was favorable to the removal of RGM and Hg P 2.5 in the atmosphere, this was probably the reason for lower RGM and Hg P 2.5 concentrations during 2527 September as compared to those observed during 2022 September (see Fig. 2).…”
Section: Daily Variation Of Hg P 25mentioning
confidence: 85%
See 1 more Smart Citation
“…On the one hand, high wind speed may increase the levels of halogen atoms (Br and Cl etc.) and sea salt aerosols in the marine atmosphere, which in turn were favorable to the production of RGM and formation of Hg P 2.5 (Auzmendi-Murua et al, 2014); on the other hand, high wind speed was favorable to the removal of RGM and Hg P 2.5 in the atmosphere, this was probably the reason for lower RGM and Hg P 2.5 concentrations during 2527 September as compared to those observed during 2022 September (see Fig. 2).…”
Section: Daily Variation Of Hg P 25mentioning
confidence: 85%
“…Numerous previous studies have shown that Hg 0 in the marine boundary layer (MBL) can be rapidly oxidized to form RGM in situ (Hedgecock et al, 2003;Laurier et al, 2003;Sprovieri et al, 2003Sprovieri et al, , 2010Laurier and Mason, 2007;Soerensen et al, 2010a;Wang et al, 2015). Ozone and OH could potentially be important oxidants on aerosols (Ariya et al, 2015), while the reactive halogen species (e.g., Br, Cl and BrO, generating from sea salt aerosols) may be the dominant sources for the oxidation of Hg 0 in the MBL (Laurier et al, 2003;Sander et al, 2003;Holmes et al, 2006Holmes et al, , 2010Seigneur and Lohman, 2008;Auzmendi-Murua et al, 2014;Gratz et al, 2015;Steffen et al, 2015;Shah et al, 2016;Horowitz et al, 2017). The wet and dry deposition (direct or uptake by sea-salt aerosol) represents a major input of RGM and Hg P to the sea and ocean due to their special and unique characteristics (i.e., high reactivity and water solubility) (Lindberg and Stratton, 1998;Landis et al, 2002;Mason and Sheu, 2002;Holmes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A trailing effect is often observed, especially with a limited number of measurements or short sampling period, since PSCF evenly distributes weight along the path of trajectories so that PSCF results often identify areas upwind and downwind of real sources as a source area . However, it should be also noted that the marine boundary layer provides good conditions for active Hg oxidation reactions due to an abundance of oxidants (Auzmendi-Murua et al, 2014); therefore, the possibility of areas over the ocean being a GOM source should not be excluded. It should be noted that different temporal resolutions for trajectories (hourly) and concentrations (every 12 h) were used for GOM and PBM.…”
Section: Pscf Resultsmentioning
confidence: 99%
“…and proposed Y ≡ OH and Br as effective radicals to carry out the second stage of oxidation to Hg II . The Cl atom can also oxidize Hg 0 to produce HgCl (Balabanov and Peterson, 2003;Donohoue et al, 2005). found that a broad range of radical oxidants could oxidize HgBr and HgCl including Y ≡ NO 2 and HO 2 , the most abundant atmospheric radicals, as well as Y ≡ BrO, ClO, and Cl.…”
Section: Chemical Mechanismmentioning
confidence: 99%